Peran Media Pembelajaran Monopoli Matematika terhadap Motivasi Belajar Siswa Sekolah Dasar - Afifah, Jihan; Suryatin, Suryatin; Al Fath, Ayatullah Muhammadin (Scholarly Journal of Elementary School, 2023)
This study aims to find out how the role of monopoly mathematics learning media to learning motivation of fifth grade students at SDN 2 Hadiwarno in mathematics learning, especially on speed and discharge material. The research method was descriptive qualitative research. The subjects this study were 12 students and a teacher class of V. The data collection method were observation, interview, and documentation. Test the validity of the data used triangulation sources and triangulation techniques. Data analysis techniques used Miles and Huberman data analysis model. The results showed that monopoly mathematics learning media was an important positive role in learning motivation of fifth grade students at SDN 2 Hadiwarno.  It was a  role in increasing student learning motivation by attracting attention of students that makes them focus on participating learning. In addition, students more active in participating learning. Increasing student motivation in learning can be seen from enthusiasm, keep spirit, independence, curiosity, and determination to face difficulties better than before using the media.